The Impact of Stigma of Loneliness on Psychological Distress in Older Adults: The Chain Mediating Effect - Fan Z; Shi X; Leng J; Cui D; Li D (Psychology Research and Behavior Management)
Zhiguang Fan,1 Xiaoli Shi,2 Jiaqi Leng,3 Dan Cui,3 Deming Li4 1Department of Psychology, Shaoxing University, Shaoxing, People’s Republic of China; 2Department of Psychology, University of Exeter, Exeter, UK; 3School of English, Jilin International Studies University, Changchun, People’s Republic of China; 4Shanghai Municipal Institute for Lifelong Education, East China Normal University, Shanghai, People’s Republic of ChinaCorrespondence: Deming Li, Email lideming0513@163.comObjective: Loneliness and psychological distress are serious challenges for older adults to cope with and factors threatening life quality and happiness during their remaining years. Older people’s attitudes and evaluations towards loneliness potentially affect psychological distress. Therefore, the current study aimed to examine the relationship between the stigma of loneliness and the psychological distress of older adults, further exploring the mediating effect of distress disclosure and loneliness.Methods: Conducted during February and March 2024, the questionnaire survey included 933 older adults (age 65– 89) using the Stigma of Loneliness Scale (SLS), Distress Disclosure Index (DDI), UCLA Loneliness scale (ULS-6), and 6-item Kessler Psychological Distress Scale (K6). The obtained data were for descriptive statistical analysis, correlation analysis, and chain mediation model testing.Results: Stigma of loneliness was significantly positively correlated with loneliness and psychological distress (r=0.61– 0.69, p< 0.01), and distress disclosure was negatively correlated with stigma of loneliness, loneliness, and psychological distress (r=− 0.37–− 0.48, p< 0.01). Stigma of loneliness can not only directly affect the psychological distress of older adults (effect value=0.38), but also indirectly affect psychological distress through the mediating roles of distress disclosure (effect value=0.04) and loneliness (effect value=0.20), and the chain mediating effect of the two (effect value=0.05).Conclusion: The study redounds to the in-depth understanding of the effect of the stigma of loneliness on psychological distress among older people and its internal mechanism. The research results contribute to theoretical reference in explaining the formation background of psychological distress among older cohorts, which intends to provide empirical evidence for intervention studies of reducing psychological distress.Keywords: older adults, stigma of loneliness, psychological distress, distress disclosure, loneliness